Global Investigation of TBL Gene Family in Rose (Rosa chinensis) Unveils RcTBL16 Is a Susceptibility Gene in Gray Mold Resistance - Tian, Yu; Zhang, Shiya; Liu, Xintong; Zhang, Zhao (Frontiers in Plant Science, 2021)
The TRICHOME BIREFRINGENCE-LIKE (TBL) family is an important gene family engaged in the O-acetylation of cell wall polysaccharides. There have been a few reports showing that TBL participated in the resistance against phytopathogens in Arabidopsis and rice. However, no relevant studies in rose (Rosa sp.) have been published. In this study, a genome-wide analysis of the TBL gene family in rose was presented, including their phylogenetic relationships, gene structure, chromosomal positioning, and collinearity analysis. The phylogenetic analysis revealed a total of 50 RcTBL genes in the rose genome, and they are unevenly distributed across all seven chromosomes. The occurrence of gene duplication events suggests that both the whole genome duplication and partial duplication may play a role in gene duplication of RcTBLs. The analysis of Ka/Ks showed that the replicated RcTBL genes underwent mainly purifying selection with limited functional differentiation. Gene expression analysis indicated that 12 RcTBLs were down-regulated upon the infection of Botrytis cinerea, the causal agent of the gray mold disease of rose. These RcTBLs may be a sort of candidate genes for regulating the response of rose to B. cinerea. Through virus-induced gene silencing, RcTBL16 was shown to be associated with susceptibility to gray mold in rose. Through this study, meaningful information for further studies on the function of the TBL protein family in rose is provided.